A conceptual model for empowering faculty members of third-generation universities of medical sciences. Issue 2 (April 2023) - Hajimiri, Khadijeh; Moradi, Mahmood; Hosseini, Elham; Jafari, Mostafa; Nasehi, Leila
الملخص: أهداف البحث: يجب أن تكون جامعات الجيل الثالث قادرة على أن تكون مستقلة وأن تعد طلابها لتلبية احتياجات المجتمع ودخول سوق العمل. في الواقع، الأداء المتوقع منهم هو تطبيق البحث في المجتمع. على الرغم من الدور الحاسم للموظفين وخاصة أعضاء هيئة التدريس في التحرك نحو جامعات الجيل الثالث، فضلا عن ضرورة تمكين الموظفين، إلا أنه تم إجراء عدد قليل من الدراسات حول تمكين أعضاء هيئة التدريس (أعضاء هيئة التدريس). هدفت هذه الدراسة إلى تصميم نموذج تصوري لتمكين أعضاء هيئة التدريس في جامعات العلوم الطبية وتسهيل الانتقال إلى جامعات الجيل الثالث. طرق البحث: تم اعتماد منهج النظرية المتجذرة لإجراء هذه الدراسة النوعية. تم اختيار ما مجموعه 11 من أعضاء هيئة التدريس من ذوي الخبرة في ريادة الأعمال كعينة باستخدام أخذ العينات الهادف. تم جمع البيانات باستخدام المقابلات شبه المنظمة، وتم إدخال البيانات التي تم الحصول عليها في برنامج حاسوبي مصمم للبيانات النوعية والمختلطة بمساعدة الكمبيوتر. النتائج: تم تلخيص المفاهيم المحددة في عملية الترميز وتصنيفها إلى خمس مجموعات وسبع فئات رئيسية. تم تصميم النموذج التصوري بعد ذلك بمجموعة من العوامل السببية (بما في ذلك هيكل نظام التعليم، والتوظيف، والتدريب، والاستثمار)، وعوامل الهيكل والسياق (بما في ذلك الهيكل والعلاقة)، والعوامل المتداخلة (بما في ذلك أنظمة الترقية والترتيب في الجامعات ونقص من الثقة المتبادلة بين الصناعة والجامعة)، فئة أساسية (خصائص أعضاء هيئة التدريس الأكفاء)، والنتيجة (جامعة الجيل الثالث). أخيرا، تم تطوير النموذج التصوري لتمكين أعضاء هيئة التدريس في جامعات الجيل الثالث من العلوم الطبية. الاستنتاجات: بناء على النموذج التصوري المصمم، فإن أهم قضية في التوجه نحو جامعات الجيل الثالث هي "خصائص أعضاء هيئة التدريس القادرين". تساعد النتائج الحالية صانعي السياسات على فهم العوامل الرئيسية التي تؤثر على تمكين أعضاء هيئة التدريس بشكل أفضل. Abstract: Background and objectives: Despite the crucial role of university staff and especially faculty members in moving towards third-generation universities, as well as the necessity of staff empowerment, only a handful of studies have been carried out on staff (especially faculty member) empowerment. This study designed a conceptual model for empowering faculty members of universities of medical sciences and facilitating transition to third-generation universities. Methods: The grounded theory approach was adopted to conduct this qualitative study. A total of 11 faculty members with entrepreneurial experience were selected as the sample using purposive sampling. The data were collected using semi-structured interviews, and the obtained data were entered into qualitative software (MAXQDA 10) for analysis. Results: The concepts identified in the coding process were summarized and classified into five groups and seven main categories. Then the conceptual model was designed with a set of causal factors (including structure of the education system, recruitment, training, and investment), structure and context factors (including structure and relationship), intervening factors (including promotion and ranking systems in universities and lack of mutual trust between industry and university), a core category (characteristics of capable faculty members), and an outcome (third-generation university). Finally, the conceptual model was developed to empower faculty members of third-generation universities of medical sciences. Conclusions: Based on the designed conceptual model, the most important issue in moving towards third-generation universities is "characteristics of capable faculty members." The present findings will help policy makers better understand the major factors affecting faculty member empowerment.